Prospective associations of maternal glycaemic insulin index and load with birth outcomes and weight status at age 5 years: results from the Lifeways Cross Generation Cohort Study. (November 2018) - Chen, Ling-Wei; Navarro, Pilar; Murrin, Celine M; Mehegan, John; Kelleher, Cecily C; Phillips, Catherine M; ,
Abstract: Background: In the face of increasing childhood obesity, identification of modifiable risk factors is urgently needed. Limited, inconclusive data have suggested quality of dietary maternal carbohydrate (glycaemic index [GI] and glycaemic load [GL]) as intervention targets. We aimed to further elucidate associations of maternal GI, GL, and insulin demand (food insulin index [II] and load [IL]) with offspring outcomes. Methods: We used data from 845 mother–child pairs recruited from two Irish hospitals. We used standard methodology to derive maternal GI, GL, II, and IL based on dietary information collected with a validated food frequency questionnaire in early pregnancy. Birth outcomes were abstracted from hospital records, and body-mass index (BMI) was determined when children were 5 years old. Multivariable regressions were used to assess the associations of maternal GI, GL, II, and IL with offspring outcomes. Ethics approval was granted by the hospitals. Findings: Mean food glycaemic and insulin indices were: GI 58·9 (SD 4·4); GL 152 (49); II 57·4 (14·4); and IL 673 (267). After adjustment for confounders, no significant associations were observed between food glycaemic and insulin indices and most birth outcomes including birthweight, birth length, BMI, macrosomia, gestational age, and head circumference. Furthermore, examination of weight status at age 5 years did not reveal any consistent significant association between either food glycaemic and insulin indices and childhood overweight and obesity. There was also no evidence of a non-linear association between these indices and the studied outcomes. Interpretation: We observed no important association of food glycaemic and insulin indices in early pregnancy with offspring birth outcomes and weight status at 5 years old that could guide intervention priority. We assessed maternal diet in only the first trimester, whereas the third trimester may be more relevant for offspring adiposity deposition. BMI is a useful adiposity indicator, but its interpretation during childhood is complicated by differential velocity and magnitude of accretion of fat-mass and fat-free mass. Future studies should use more direct methods and collect dietary information in all three trimesters to investigate the potential influence of maternal food glycaemic and insulin indices on offspring body composition. Funding: Irish Health Research Board (reference HRC/2007/13).